Usage of Social Media Tools by Library and Information Science (LIS) Students in Nigerian library schools - Orubebe, Ebiere; Okeke, Oluchi; Oladokun, Bolaji; Uchendu, Benedicta (International Journal of Knowledge Content Development & Technology, 2025)
This study investigated the use of social media tools by LIS students in Nigerian library schools. In so doing, the study examines the types of social media platforms utilized by Library and Information Science (LIS) students, the most commonly visited sites, and the challenges associated with social media use. A descriptive survey design was employed, and convenient sampling was used to select 248 LIS undergraduate students from five Nigerian universities. A structured questionnaire, validated by experts, was the primary instrument for data collection. The findings reveal that WhatsApp, TikTok and YouTube are the most frequently utilized platforms for communication, content consumption, and interaction, while professional and educational tools like LinkedIn and Microsoft Teams are less commonly used. The most significant challenge faced by students is the high cost of internet access, which limits their engagement with social media. Other challenges include misinformation, poor connectivity, and lack of computer literacy. The study recommends that educational institutions integrate both socially engaging and professional platforms into the academic process and develop policies to make internet access more affordable. Further, promoting digital literacy and responsible social media use is essential for improving student engagement and academic performance.